EVALUASI PENGELOLAAN DAN PERTANGGUNGJAWABAN ALOKASI DANA DESA DI DESA EKOAE KECAMATAN WEWARIA KABUPATEN ENDE - Benge, Aloysius Redemtus; Sayang, Sabulon; Ismail, Nuraini (Program Studi Akuntansi Universitas Flores, 2023)
According to the regulation of the Minister of Home Affairs Number 20 of 2018 Village Funds are funds sourced from the APBN (State Revenue Expenditure Budget) which are calculated for villages that are transferred through the district/city APBD (Regional Revenue Expenditure Budget) and are used to finance regional administration, implementation of development , social scanning, and community empowerment. The research method used is descriptive research using observational data collection techniques, interviews, documentation and literature study. The results of the study show that the management of Village fund allocations in Ekoae Village, Wewaria District, Ende Regency is in accordance with Permendagri NO 20 of 2018.